Chemical Constituents from the Fruits of Cicuta virosa L. var. latisecta Celak - Li, Zhen-Lin; Qian, Shi-Hui; Pu, She-Ban; Zhang, Jing-Yan (Asian Journal of Chemistry, 2012)
In this paper, the chemical constituents from the fruits of Cicuta virosa L. var latisecta Celak were isolated and characterized. Isolation and purification were carried out on the column chromatography of silica gel and Sephadex LH-20. Twelve compounds were isolated and identified as rel-(3S, 4S, 5S)-3-[(2R)-2-hydroxydocosanoyl-pentacosanoylaminol]-4-hydroxyl- 5-[(4Z)-tetradecane-4-ene]-2, 3, 4, 5-tetra-hydrofuran (1a-1d mixture), quercetin (2), isorhamnetin (3), isorhamnetin-3-O-b-D-glucopyranoside (4), (24R)-cycloart-25-ene-3,24-diol (5) and (24S)-cycloart-25-ene-3,24-diol (6) mixture, (6H,7H)-a-spinasterone (7), 2,3- dihydrooenanthetol (8) and n-tricasanoic acid (9).